Complex segregation analysis of nonsyndromic Cleft Lip/Palate in Antioquia, Colombia - Moreno, Lina; Lidral, Andrew; Fonseca, Idalyd; Valencia, Consuelo; Arcos-Burgos, Mauricio (Actualidades Biológicas, 2017)
The present study was undertaken to examine the pattern inheritance of Cleft Lip/Palate (CLP) in pedigrees ascertained from Antioquia, Colombia. Ninety-five extended and multigenerational pedigrees, constituted by 201 nuclear components and 1.136 records were analyzed. Ten hypothetical models were contrasted using likelihood ratio tests. The hypotheses of no familial transmission, multifactorial component compared against that of the existence of a major gene only, the existence of a recessive major gene, that of non major component in the mixed model and that of the non transmission of major effect (t1 = t2 = t3) were rejected. In contrast, hypotheses postulating a major locus (dominant, codominant) and that of no polygenic component in the mixed model could not be rejected. Iteration of the parameter t2 was the most parsimonious. Thus far, the most parsimonious model is that of a major gene (dominant, codominant) without multifactorial effects but, taking into account, that the t2 iteration in the major gene model with unrestricted d, result in a significantly improving of the model likelihood, oligogenic interactions can not be underrated.